Proximal Fibular Osteotomy - Simplest and Most Effective Mean to Delay Total Knee Arthroplasty - Naseem Munshi; Badaruddin Sahito; Muhammad Khalid Arain; Sabia Aziz; Remsha Sattar (ziauddin University, 2024)
Background: Osteoarthritis involves degeneration of articular cartilage seen with increasing age. The knee joint, the most common joint that falls prey to attacks of osteoarthritis, has 30% incidence in population above 60 years. Total knee arthroplasty (TKA) is the main surgical option for orthopaedics. Though it corrects the deformity and relieves pain, yet it is not the treatment of choice in younger population. This study aimed to validate the effects of proximal fibular osteotomy (PFO) as a newer technique in managing medial compartment knee osteoarthritis. Methods: The diagnosed patients for medial compartment knee joint osteoarthritis were selected for study from Dr. Ziauddin University hospital of Karachi. Excluded were aged less than 40 years, or with BMI more than 30, and patients with tri-compartmental arthritis. Medial and lateral joint spaces along with Oxford knee score were measured and recorded pre- and post-operatively. Patients underwent PFO after giving written and informed consent. Results: Total number of patients selected was 30 for this study; 21 (70%) females, and 9 (30%) males (mean age 58.8 years). Mean pre-operative measured medial joint space on standard antero-posterior (AP) radiograph was 0.442± 0.04 cm. Mean recorded pre-operative Oxford knee score was 23.87±3.74 mm. Improvement was observed in mean postoperative medial joint space to 0.572± 0 .066 cm and mean post-operative Oxford knee score to 40.2±5.8mm. Conclusion: This study concludes that PFO significantly improves joint function in patients with medial compartment osteoarthritis knee and may delay the need for total knee arthroplasty, if carried out at an appropriate stage. Keywords: Osteotomy; Osteoarthritis; Total Knee Arthroplasty.